Penatalaksanaan Holistik Pada Wanita Usia 63 Tahun Dengan Penyakit Osteoarthritis dengan Hipertensi dan Dispepsia Melalui Pendekatan Kedokteran Keluarga - thaharatin Giza; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2022)
Osteoarthritis is a chronic disease characterized by damage of joint cartilage that causing stiffness, pain, and movement disorders. While hypertension is a condition where a person’s systolic and diastolic blood pressure is >140/90 mmHg. Both osteoarthritis and hypertension are diseases that must be managed comprehensively because they are chronic. Implementing family doctor services by identifying risk factors, clinical problems, as well as patient management based on evidence-based medicine that is family-approach, patient-centred dan community oriented. The study conducted is a case report. Patient, Mrs. S, a woman, 63 years old, has a complaint of pain in both knee joints since about 3 days ago. Pain felt come and go and getting worse especially in the morning with a duration is about 15 minutes. The patient has an additional complaint of headache and epigastric pain. The patient was diagnosed as osteoarthritis with hypertension and dyspepsia. Several factors can affect patient’s condition, both internal and external risk factors. In this case, diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was a decrease in clinical symptoms and an increase in the knowledge of patients and their families. The diagnosis of osteoarthritis with hypertension and dyspepsia in this patient was in accordance with the theory from several guidelines and journals, it was seen that there were a change in knowledge of the patient and his family after the intervention based on evidence-based medicine yang bersifat patient-centred dan family medicine approach.